Management and legacy of the Brazil 2014 Fifa World Cup during its candidacy bid - Rômulo Meira Reis; André Malina; Lamartine Pereira Dacosta; Silvio de Cássio Costa Telles
Abstract Aim: Sporting mega-event organization requires developing strategies to maximize the chance of success. For the Brazil 2014 Fifa World Cup, it was not different. The action started long before the opening match on 06/12/2014. The issue we seek to investigate is: How did the 2014 Fifa World Cup's management as a sporting mega-event develop during the pre-event phase? The general objective was to identify and analyze management-related peculiarities of the 2014 Fifa World Cup's management during the pre-event period. The operational objectives were: (i) To identify the organizational structure set up to manage the 2014 Fifa World Cup; (ii) reveal the candidacy process; (iii) find out the initial budgets/investments planned for the 2014 Fifa World Cup; (iv) examine the management difficulties that happened during the pre-event period; and (v) detect the legacy left by said phase. Method: primary data was collected through an elite interview conceded by ex-Minister of Sports Orlando Silva and secondary data was obtained through bibliographical and documental research techniques. The interview was evaluated through content analysis. The analysis and discussion were categorized as follows: organizational structure, candidacy process, management, and legacy. The results show legacy was obtained in the pre-event phase due to the knowledge generated during the candidacy process. They also show a strengthening of Brazil's image as a mega-event organizer. Some difficulties include no integration between organizers, delay in defining host-cities and construction, no initial budgets and no transparency in the bid's initial publishing.